A homozygous mutation of VWA3B causes cerebellar ataxia with intellectual disability. Issue 6 (8th July 2015) - Kawarai, Toshitaka; Tajima, Atsushi; Kuroda, Yukiko; Saji, Naoki; Orlacchio, Antonio; Terasawa, Hideo; Shimizu, Hirotaka; Kita, Yasushi; Izumi, Yuishin; Mitsui, Takao; Imoto, Issei; Kaji, Ryuji
Abstract : Background: Hereditary cerebellar ataxia constitutes a heterogeneous group of neurodegenerative disorders, occasionally accompanied by other neurological features. Genetic defects remain to be elucidated in approximately 40% of hereditary cerebellar ataxia cases in Japan. We attempted to identify the gene responsible for autosomal recessive cerebellar ataxia with intellectual disability. Methods: The present study involved three patients in a consanguineous Japanese family. Neurological examination and gene analyses were performed in all family members. We performed genome-wide linkage analysis including single nucleotide polymorphism arrays, copy-number variation analysis and whole exome sequencing. To clarify the functional alteration resulting from the identified mutation, we performed cell viability assay of cultured cells expressing mutant protein. Results: One homozygous region shared among the three patients on chromosomes 2p16.1–2q12.3 was identified. Using whole exome sequencing, six homozygous variants in genes in the region were detected. Only one variant, VWA3B c.A1865C, results in a change of a highly conserved amino acid (p.K622T) and was not present in control samples. VWA3B encodes a von Willebrand Factor A Domain-Containing Protein 3B with ubiquitous expression, including the cerebellum. The viability of cultured cells expressing the specific K622T mutation was proved to decrease through the activation of apoptotic pathway. Conclusions: Mutated VWA3B was found to be likely associated with cerebellar degeneration with intellectual disability. Although a rare cause of cerebellar degeneration, these findings indicate a critical role for VWA3B in the apoptosis pathway in neuronal tissues.